Heat Shock Proteins and Their Role in Pregnancy: Redefining the Function of “Old Rum in a New Bottle” - Jee, Babban; Dhar, Ruby; Singh, Sunil; Karmakar, Subhradip (Frontiers in Cell and Developmental Biology, 2021)
Pregnancy in humans is a multi-step complex physiological process comprising three discrete events, decidualization, implantationand placentation. Its overall success depends on the incremental advantage that each of the preceding stages passes on to the next. The success of these synchronized sequels of events is an outcome of timely coordination between them. The pregnancy events are coordinated and governed primarily by the ovarian steroid hormones, estrogen and progesterone, which are essentially ligand-activated transcription factors. It's well known that intercellular signaling of steroid hormones engages a plethora of adapter proteins that participate in executing the biological functions. This involves binding of the hormone receptor complex to the DNA response elements in a sequence specific manner. Working with Drosophila melanogaster, the heat shock proteins (HSPs) were originally described by Ferruccio Ritossa back in the early 1960s. Over the years, there has been considerable advancement of our understanding of these conserved families of proteins, particularly in pregnancy. Accumulating evidence suggests that endometrial and uterine cells have an abundance of HSP27, HSP60, HSP70 and HSP90, implying their possible involvement during the pregnancy process. HSPs have been found to be associated with decidualization, implantation and placentation, with their dysregulation associated with implantation failure, pregnancy loss and other feto-maternal complications. Furthermore, HSP is also associated with stress response, specifically in modulating the ER stress, a critical determinant for reproductive success. Recent advances suggest a therapeutic role of HSPs proteins in improving the pregnancy outcome. In this review, we summarized our latest understanding of the role of different members of the HSP families during pregnancy and associated complications based on experimental and clinical evidences, thereby redefining and exploring their novel function with new perspective, beyond their prototype role as molecular chaperones.